2008
DOI: 10.1038/sj.bjc.6604717
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression of KLK6 and KLK10 as prognostic factors for survival in pancreatic ductal adenocarcinoma

Abstract: Kallikreins play an important role in tumour microenvironment and as cancer biomarkers in different cancer entities. Previous studies suggested an upregulation of KLK10 and KLK6 in pancreatic ductal adenocarcinoma (PDAC). Therefore, we evaluated the clinicopathological role of these kallikreins and their value as biomarkers in PDAC. Differential expression was validated by DNA-microarrays and immunohistochemistry in normal and malignant pancreatic tissues. Sera concentrations of both kallikreins were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
47
1
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 30 publications
10
47
1
5
Order By: Relevance
“…These results are similar to previous studies that found increased expression of KLK6 in primary pancreatic ductal adenocarcinoma (Ruckert et al, 2008) and salivary gland tumours (Darling et al, 2006), but found no significant association with survival. Kallikreins 6 and 13 are expressed in normal epithelium (Petraki et al, 2001(Petraki et al, , 2003, including the OSE as we have shown here.…”
Section: Discussionsupporting
confidence: 91%
“…These results are similar to previous studies that found increased expression of KLK6 in primary pancreatic ductal adenocarcinoma (Ruckert et al, 2008) and salivary gland tumours (Darling et al, 2006), but found no significant association with survival. Kallikreins 6 and 13 are expressed in normal epithelium (Petraki et al, 2001(Petraki et al, , 2003, including the OSE as we have shown here.…”
Section: Discussionsupporting
confidence: 91%
“…Both factors have been shown to have an effect on cell motility. Co-expression of kallikrein 6 and kallikrein 10 in native tumor tissue is also correlated with poor survival [17]. We were, therefore, interested to determine if these factors were expressed in our cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-2 and lymph node status combined was more powerful than pathologic status alone (27). Further studies, in which no individual marker was prognostic, yielded independently prognostic groups of markers, for example, KLK6 and KLK10 (152).…”
Section: Discussionmentioning
confidence: 99%